Recycling of Aircraft: State of the Art in 2011. (2nd January 2013) - Asmatulu, Eylem; Overcash, Michael; Twomey, Janet
Abstract : Recently, the end-of-service life for aging aircraft and related parts has become a key subject in recycling industries worldwide. Over the next 20 years, approximately 12, 000 aircraft currently utilized for different purposes will be at the end of service. Thus, reclaiming retired aircraft by environmentally responsible methods while retaining some of the value becomes a significant need. Recycling aircraft components and using these in different applications will reduce the consumption of natural resources as well as landfill allocations. Compared to the production of virgin materials, recycling aircraft will also reduce air, water, and soil contaminations, as well as energy demand. In the present study, we have investigated the environmental benefits of recycling and reusing aircraft components in the same or similar applications as low-energy input materials. During the aircraft recycling, most of the aircraft components can be recycled and reused after reasonable modifications and investments.